2020
DOI: 10.1088/1748-605x/ab712e
|View full text |Cite
|
Sign up to set email alerts
|

Dual-enzymatically crosslinked hyaluronic acid hydrogel as a long-time 3D stem cell culture system

Abstract: Stem cell-based tissue engineering shows enormous potential for regenerative medicine. Threedimensional (3D) stem cell culture is the most basic aspect of tissue engineering. However, achievement of a perfect scaffold for highly efficient 3D cell culture is currently still limited. Herein, a new hyaluronic acid hydrogel dual-enzymatically crosslinked by horseradish peroxidase and choline oxidase is developed as a 3D stem cell culture system. This hydrogel possesses superior stability over two months, controlla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Tyramine was grafted onto the HA chain to obtain HT conjugate according to our previous method [ 16 ]. Briefly, the HA sodium salt was dissolved in 100 mL of MES solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyramine was grafted onto the HA chain to obtain HT conjugate according to our previous method [ 16 ]. Briefly, the HA sodium salt was dissolved in 100 mL of MES solution.…”
Section: Methodsmentioning
confidence: 99%
“…HT has already been developed as a protein drug delivery system [ 12 , 13 ], and is widely used in tissue engineering [ 14 , 15 ]. It offers the advantages of cell compatibility, biodegradability, and non-immunogenicity [ 16 ]. Chitosan (CS) is a natural polysaccharide prepared by the deacetylation of chitin [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The porous structure of the hydrogel enables substance exchange and cell entrance at the initial stage as well as vascular ingrowth in the follow-up stage. It has been substantially shown that cells are easily suspended within hydrogels, and the viability of the encapsulated cells is highly preserved (Gao et al, 2020;Paez et al, 2020).…”
Section: The Preponderance Of Hydrogels In Bone Tissue Engineeringmentioning
confidence: 99%
“…Scaffold 3D systems consist in a structural support that favours cell adhesion, proliferation, migration, cell-to-cell interaction and signalling [33] , [34] . Natural scaffolds are based on molecules that are present in the ECM such as collagen, gelatine and derivatives [35] , [36] , complex matrix (e.g., commercial Matrigel™) and hydrogels [37] , [38] , and polysaccharides as alginate, chitosan or hyaluronic acid [39] , [40] , [41] , [42] , [43] . Whereas the main advantage of these natural scaffolds is their biocompatibility, their production and inter-batches variability are the main issues of these materials.…”
Section: Introductionmentioning
confidence: 99%